Credit market disequilibrium in Greece (2003-2011) - a Bayesian approach - Angelos Vouldis (European Central Bank (ECB), 2015)
Motivated by the linkage between credit and growth in the Greek economy, and the deceleration of credit since the financial crisis, this paper studies the evolution of credit demand and supply in Greece. A disequilibrium model of demand and supply is estimated spanning the period 2003M1-2011M3. The adopted specification allows for stochastic shocks on both supply and demand. A Bayesian estimation methodology with data augmentation for the latent variables is used. The analysis is carried out separately for each type of loan (short- and long-term business loans, consumer loans and mortgages) enabling the comparative study of the credit rationing and supply constraint effects among loan categories. The results indicate that, for all loan categories, excess demand characterized the boom period. After the intensification of the debt crisis, evidence is provided for the existence of excess demand due to binding constraints on supply. However, demand for short-term business loans has slowed down more than supply, reflecting businesses' need for stable funding.
Keywords: D50; E44; E42; C32; G21; G28; P00; 330; Bayesian methods; Credit disequilibrium; Greek credit market; Leading indicators; Stress test